Reliability and validity of the Female Sexual Function Index administered via telephone in Brazilian women - Wolpe, Raquel Eleine; Wittkopf, Priscilla Geraldine; Martins, Matheus Pereira Peres; Moreira, Géssica Maria; Rosa, Suellen Bitencourt; Sperandio, Fabiana Flores (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Women’s sexuality is influenced by anatomical, physiological, psychological and cultural factors. It is likely that questionnaires comprehensively evaluate women´s sexual aspects. The Female Sexual Function Index (FSFI) is considered a gold standard instrument to assess female sexual function. The validation of the administration of this questionnaire via telephone has a high research and clinical importance. Objectives: The aim of this study was to evaluate the validity and reliability of the FSFI administered via telephone in Brazilian women. Methods: 51 women answered the FSFI by telephone and paper with an interval of one week between both administrations. After two weeks of the application via telephone (test), the questionnaire was administered again, also via telephone (retest), to verify the reliability. the Spearman’s rank correlation index was used to estimate the relationship between FSFI-phone and FSFI-paper. Intraclass correlation coefficient (ICC) was used to assess the FSFI-phone reliability (test-retest). Results: The Spearman’s rank test showed a high correlation between the total scores of the FSFI-phone and FSFI-paper with value of 0.96. Correlations between the questions and domains were conducted in pairs, which reached levels higher than 0.70. The ICC values were even higher (ICC> 0.90). Conclusions: These preliminary results, showed that the FSFI questionnaire administered via telephone is a valid, reliable and responsive method that facilitates quality assurance and can potentially reduce human resource costs in data acquisition. The use of FSFI administered via telephone addresses a logistic need for patient and physician, by providing fast and safe information convenient to both patient and practitioner.